2020
DOI: 10.1016/j.ijom.2019.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable versus titanium osteosynthesis in maxillofacial traumatology: a systematic review with meta-analysis and trial sequential analysis

Abstract: Titanium osteosynthesis is currently the fixation system of choice in maxillofacial traumatology.Biodegradable osteosynthesis systems have the ability to degrade in the human body. The aim of this study was to conduct a systematic review, with meta-and trial sequential analyses, to assess the efficacy and morbidity of biodegradable versus titanium osteosyntheses after maxillofacial trauma. MEDLINE, EMBASE, and CENTRAL were searched for randomized controlled trials, and prospective and retrospective controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(55 citation statements)
references
References 58 publications
0
55
0
Order By: Relevance
“…poly‐L‐lactic or polyglycolic acid) and may reduce removal rates of these osteosynthesis systems in a second operation while also avoiding the disadvantages of titanium osteosyntheses. Biodegradable systems have, however, their own limitations including lower strength and stiffness [ 9 ] that could lead to higher malunion rates and less skeletal stability after orthognathic surgery, palpability due to bulkiness, [ 10 ] and possible foreign body reactions [ 11 ]. As a consequence, biodegradable implants are removed in up to 17% of the cases in a second operation [ 2 , 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…poly‐L‐lactic or polyglycolic acid) and may reduce removal rates of these osteosynthesis systems in a second operation while also avoiding the disadvantages of titanium osteosyntheses. Biodegradable systems have, however, their own limitations including lower strength and stiffness [ 9 ] that could lead to higher malunion rates and less skeletal stability after orthognathic surgery, palpability due to bulkiness, [ 10 ] and possible foreign body reactions [ 11 ]. As a consequence, biodegradable implants are removed in up to 17% of the cases in a second operation [ 2 , 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradable systems have, however, their own limitations including lower strength and stiffness [ 9 ] that could lead to higher malunion rates and less skeletal stability after orthognathic surgery, palpability due to bulkiness, [ 10 ] and possible foreign body reactions [ 11 ]. As a consequence, biodegradable implants are removed in up to 17% of the cases in a second operation [ 2 , 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this study shows that the newer CrossDrive (2018) and MaxDrive osteosynthesis systems remain to have higher mechanical properties than the tested biodegradable osteosynthesis systems. However, as clinical studies have shown that biodegradable and titanium osteosynthesis systems have similar efficacy in maxillofacial traumatology 9 , both systems have mechanical properties that suffice for clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…When also considering the dimensions and volumes, and the (co-)polymer compositions of these two systems, the SonicWeld Rx/Rx system is preferred as it is less bulky (i.e., − 14% in volume) and has a more favourable degradative copolymer composition 13,59 . Whenever low pull-out forces are expected, we recommend not tapping the SonicPins burr holes as this remains an extra perioperative, time-consuming step for surgeons 9 . On the other hand, whenever high torsional forces are expected (e.g., fixating mandibular symphysis fractures 41 ), the Inion CPS 2.5 mm system is recommended although it might be bulky due to the plate and screw dimensions.…”
Section: Indicationsmentioning
confidence: 99%
“…It was demonstrated that the possibility of intraoperative switches due to the material failure of the bioabsorbable system also reduced the justification of the use of absorbable plates and screws in maxillofacial surgery [ 65 ]. Furthermore, in another meta-analysis, it was reported that perioperative screw breakage was more frequent in the bioabsorbable osteosynthesis group than the titanium osteosynthesis group [ 66 ]. Eventually, due to these limitations and complications of polymer-based absorbable osteofixation materials, there is a desire for materials with higher strength while having the advantages of absorbable osteosynthesis, and Mg is in the spotlight as a material which can satisfy such conditions.…”
Section: Conventional Bioabsorbable Plates and Screwsmentioning
confidence: 99%